Damping and ventilating exhaust sole and preparation method thereof
By setting up a connecting cavity structure inside the shoe body and using specific materials to combine it, the problem that existing soles are difficult to achieve overall good shock absorption and ventilation effects after long or high-intensity exercise is solved, and the comprehensive performance improvement of the soles is achieved and improve durability.
Patent Information
- Application Number
- CN202411594497.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-09
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-09
AI Technical Summary
The existing shock-absorbing and breathable soles are difficult to achieve overall good shock-absorbing and ventilation effects after long or high-intensity exercise, which affects the comfort of wearing and durability of the soles.
By setting up several interconnected cavity structures inside the shoe body, and combining EVA latex and polyurethane prepolymers, combining expanded graphite, carbon nanotubes, island fibers, porous nanosilicon dioxide and other fillers, the sole is enhanced Comprehensive performance.
It achieves better cushioning and shock absorption performance, wear resistance and breathability, reduces the possibility of cavity structure deformation, and improves the comfort and durability of the sole.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of shoe processing, and more specifically, to a shock-absorbing and ventilating ventilated sole and a preparation method thereof. Background Art
[0002] In recent years, with the improvement of people's living standards and the enhancement of health awareness, the demand for sports shoes has been increasing. In order to meet the needs of different sports and pursue a more comfortable wearing experience, the design and manufacturing of sports shoes have also tended to be refined and functional. Especially in the design of the sole, not only its cushioning and shock absorption performance should be considered, but also the wearing comfort, breathability and durability should be paid attention to, which not only improves the wearer's sports performance, but also improves the health attributes of sports shoes.
[0003] At present, in order to improve the shock absorption and ventilation performance of the sole, sports shoe manufacturers usually add a combination of multiple materials to the sole, or change the sole structure to achieve this. For example, elastic materials such as EVA, TPU, etc. are used to enhance the shock absorption effect of the sole, or an air cushion structure is added to improve the cushioning performance of the sole; at the same time, air holes are set or special materials are used to enhance the ventilation and air permeability of the sole. The application of the above structures or materials has improved the comprehensive performance of the sole to a certain extent.
[0004] However, existing shock-absorbing and breathable soles are mostly provided with ventilation holes in part of the sole or are made of a single material. This method is difficult to achieve good overall shock absorption and ventilation effects in actual use, especially after long-term or high-intensity exercise, the moisture in the shoe is not easy to discharge, affecting the wearing comfort and the durability of the sole. Summary of the invention
[0005] In order to obtain better cushioning and shock absorbing performance and wear resistance, while achieving better ventilation performance and improving the comfort and durability of the sole, the present application provides a shock absorbing and ventilation venting sole and a preparation method thereof.
[0006] In the first aspect, the present application provides a shock-absorbing and ventilating ventilating sole, comprising a shoe body, wherein a plurality of interconnected cavity structures are arranged inside the shoe body, and the shoe body is made of raw materials in the following weight percentages: EVA latex 25-50% Polyurethane prepolymer 24-50% Chain extender 5-15% Dispersant 1-8% Processing aids 1-3% Filler 1-20%; The total weight percentage of the EVA latex, polyurethane prepolymer, chain extender, dispersant, processing aid and filler is 100%; The filler is one or more of expanded graphite, carbon nanotubes, sea-island fibers, and porous nano-silicon dioxide.
[0007] In the above technical solution, the cavity structure is formed to make the sole have better ventilation and shock absorption and buffering effects. The shoe body adopts EVA latex and polyurethane prepolymer compound, which gives full play to the synergistic effect of the two, improves the comprehensive performance of the sole, and makes the sole have excellent elasticity and bearing capacity; combined with one or more of expanded graphite, carbon nanotubes, sea island fibers, and porous nano-silica as fillers, it plays a role in enhancing support and elasticity, effectively preventing the deformation of the cavity structure of the sole during use, and effectively ensuring ventilation and shock absorption effects.
[0008] The filler is evenly dispersed in the EVA latex and the polyurethane prepolymer under the action of the dispersant, and the chain extender further extends the chain of the polyurethane prepolymer to enhance its elasticity. With the assistance of the processing aid, the prepared sole has high elasticity, excellent cushioning performance, outstanding wear resistance and breathability.
[0009] In summary, one or more of expanded graphite, carbon nanotubes, sea-island fibers, and porous nano-silica are used as fillers to enhance support. Under the action of a dispersant, they are evenly mixed with polyurethane prepolymers and EVA latex, and play a synergistic role, further improving the overall performance. Under the action of a chain extender, the elasticity is further improved. With the assistance of a processing aid, the processed sole has better cushioning and shock absorption performance, wear resistance, and durability, reducing the possibility of deformation of its cavity structure after long-term use. Improve the comfort and durability of the sole.
[0010] Preferably, the filler is composed of expanded graphite, sea-island fibers, and porous nano-silica in a weight ratio of (1-2.3): (0.3-1.2): 1.
[0011] When the three materials of expanded graphite, sea-island fiber and porous nano-silica are compounded, a special filling structure is formed in the sole system. The synergistic effect makes the sole have better elasticity, wear resistance and compression resistance. At the same time, it interacts with polyurethane prepolymer and EVA latex to further improve the cushioning and shock absorption performance and wear resistance. During use, it reduces the deformation of the cavity structure, maintains a better ventilation effect, and improves the overall durability and comfort of the sole.
[0012] Preferably, the particle size of the expanded graphite is 10-30 microns, and the worm length is 50-180 microns.
[0013] Preferably, expanded graphite with a particle size of 10-30 microns and a worm length of 50-180 microns is selected, which has softness, resilience, plasticity and filling and supporting effects, and is combined with polyurethane prepolymer and EVA latex to play a synergistic role, so that the sole has better shock absorption effect, ventilation performance and wear resistance.
[0014] Preferably, the sea-island fiber has a diameter of 3-5D and a length of 0.5-1.5 mm.
[0015] The sea-island fibers of specific diameter and length are preferably selected to interact with the polyurethane prepolymer and EVA latex to play a synergistic role, thereby enhancing the mechanical properties and comfort of the sole material, thereby improving the overall shock absorption effect, breathability and wear resistance.
[0016] Preferably, the particle size of the porous nano-silica is 50-500 nm, and the particle size of the carbon nanotube is 10-100 nm.
[0017] The particle size of porous nano-silica is controlled within the range of 50-500 nanometers, and the particle size of carbon nanotubes is controlled within the range of 10-100 nanometers. They can play a filling and reinforcing role in polyurethane prepolymer and EVA latex systems, effectively improving the cushioning and shock absorption performance, wear resistance and ventilation performance of the sole material.
[0018] Preferably, the dispersant is a polyethylene glycol solution or a silane coupling agent solution.
[0019] Polyethylene glycol solution or silane coupling agent solution is selectively selected as the dispersant, which effectively improves the dispersibility and compatibility of the filler in the raw material system of the sole material, and further improves the comprehensive performance of the sole.
[0020] Preferably, the dispersant is prepared from the following raw materials in parts by weight: Polyisobutylene succinimide 0.1-0.5 parts Polyethylene glycol 0.1-0.8 parts 1. 1-3 parts of isocyanate propylmethyl dimethoxysilane Methacryloylethyl sulfobetaine 0.5-1.5 parts Benzoyl peroxide 0.01-0.03 parts 5-8 parts of ethyl acetate.
[0021] The dispersant provided by the present invention can effectively improve the dispersibility and compatibility of the filler in the sole material system by reasonably proportioning polyisobutylene succinimide, polyethylene glycol, 3-isocyanate propylmethyl dimethoxy silane, methacryloylethyl sulfobetaine and ethyl acetate, and the active groups therein further react with the active groups of the polyurethane prepolymer or the EVA latex, so that the filler is closely combined with the raw material system of the sole material. Furthermore, during use, the deformation of the cavity structure is reduced, a better ventilation effect is maintained, and the overall durability and comfort of the sole are improved.
[0022] Preferably, the dispersant is prepared by the following method: Weigh 0.1-0.5 parts of polyisobutylene succinimide, 0.1-0.8 parts of polyethylene glycol, 1-3 parts of 3-isocyanate propylmethyldimethoxysilane, 0.5-1.5 parts of methacryloylethyl sulfobetaine, and 5-8 parts of ethyl acetate, and mix them evenly to obtain a dispersant.
[0023] Through the above method, preferably, the processing aid is one or more of an antioxidant, a mold release agent, a foaming agent, a defoaming agent, and a catalyst.
[0024] The processing aids are selected from one or more of antioxidants, release agents, foaming agents, defoaming agents, and catalysts, which can effectively improve the aging resistance of the sole material, facilitate demolding, and help form a uniform foam structure, or reduce foam generation, and play a role in catalytic reactions, thereby further improving the shock absorption and ventilation performance of the sole.
[0025] In a second aspect, a method for preparing a shock-absorbing and ventilating ventilated shoe sole is prepared by the following method: Weigh 24-50% of polyurethane prepolymer, 5-15% of chain extender, and 1-3% of processing aid and mix them evenly with all the mixture A. After the reaction, add 25-50% of EVA latex and mix evenly to obtain a shoe sole slurry. The shoe sole slurry is poured into the mold and solidified to form a shoe sole embryo in the mold, and a plurality of interconnected cavity structures are formed inside the shoe sole embryo to obtain the shoe sole.
[0026] The preparation method can ensure that a uniformly distributed and interconnected cavity structure is formed inside the sole, thereby improving the shock absorption and ventilation performance of the sole. At the same time, by accurately controlling the proportion and mixing order of each component, it is beneficial to improve the overall performance of the sole material and ensure the durability and comfort of the sole. Specifically, the preparation of mixture A allows the filler and dispersant to be fully combined and further dispersed into the sole slurry, which helps to form a stable structure.
[0027] In summary, this application has the following beneficial effects: 1. By setting a number of interconnected cavity structures inside the shoe body, the overall shock absorption performance of the sole is effectively improved, while the air circulation is enhanced and the wearing comfort is improved; 2. The reasonable ratio of EVA latex, polyurethane prepolymer and other additives makes the sole have better elasticity and durability, extending the service life of the sole; 3. The selection and application of fillers further enhance the breathability and shock absorption effect of the sole, especially under long-term or high-intensity exercise conditions, which can effectively discharge moisture from the shoe and keep the shoe dry. DETAILED DESCRIPTION
[0028] The present application is further described in detail below with reference to the embodiments.
[0029] EVA latex, the manufacturer is preferably Changzhou Modern Chemical Co., Ltd., model MD-6062; The polyurethane prepolymer is an aromatic polyisocyanate prepolymer with an NCO content of 3.6-4.2%, Deshimodu MDI polyester prepolymer MDQ24163; The chain extender is 1,4-butanediol; The sea-island fiber is composed of 60-80% polyamide and 20-40% polyester by mass; The release agent is polyvinyl alcohol with a number average molecular weight of 1500-2000; The blowing agent is blowing agent H (dinitrosopentamethylenetetramine); The antioxidant is antioxidant 1010; The catalyst is dibutyltin dilaurate.
[0030] Example 1 A shock-absorbing and ventilating exhaust sole comprises a shoe body, wherein a plurality of interconnected cavity structures are arranged inside the shoe body, wherein the volume of the cavity structure accounts for 10% of the total area of the sole, and the cavity structure is located on the side of the sole close to the heel of a human body.
[0031] The exhaust sole is made by the following method: According to weight percentage, 8% of filler and 1% of dispersant are weighed and mixed evenly to obtain a mixture A; According to weight percentage, 50% of polyurethane prepolymer, 30% of chain extender, and 1% of processing aid were weighed and mixed with all the mixture A, heated to 75°C, reacted at a speed of 100 r / min for 3 hours, and then 10% of EVA latex was added, and the mixture was stirred for 1 hour to be fully mixed to obtain a shoe sole slurry; The sole slurry is placed in a vacuum degassing machine for degassing, and then poured into a sole mold, placed in a vulcanizer and pressurized to 30 MPa, and heated to 115°C. After 10 minutes, a sole embryo is formed in the mold, and a number of interconnected cavity structures are formed inside the sole embryo. The sole embryo is taken out of the mold and placed at room temperature for 24 hours to obtain a sole.
[0032] The filler is expanded graphite, the average particle size of the expanded graphite is 10 microns, and the average length of the worms is 50 microns. The dispersant is a polyethylene glycol solution, which is obtained by mixing polyethylene glycol with an average molecular weight and water in a weight ratio of 1:1. The processing aid is composed of an antioxidant, a release agent, a foaming agent, and a catalyst in a weight ratio of 3:1:5:1.
[0033] Example 2-3 The difference between Example 2-3 and Example 1 is that the amount of raw materials used is different, as shown in Table 1; Table 1 Amount of raw materials used in Examples 1-3 (%) raw material Example 1 Example 2 Example 3 EVA latex 25 30 40 Polyurethane prepolymer 50 37 24 Chain Extender 15 10 5 Dispersants 1 5 8 Processing Aids 1 2 3 Fillers 8 16 20 Example 4 The difference between Example 4 and Example 2 is that the filler is sea-island fiber, the diameter of the sea-island fiber is 3D, and the length is 0.5 mm.
[0034] Example 5 The difference between Example 5 and Example 2 is that the filler is carbon nanotubes, and the average particle size of the carbon nanotubes is 10 nm.
[0035] Example 6 The difference between Example 6 and Example 2 is that the filler is porous nano-silica, and the particle size of the porous nano-silica is 500 nm.
[0036] Example 7 The difference between Example 7 and Example 2 is that the filler is composed of expanded graphite and porous nano-silica in a weight ratio of 1:1; the particle size of the porous nano-silica is 500nm; the average particle size of the expanded graphite is 10 microns, and the average length of the worms is 50 microns.
[0037] Example 8 The difference between Example 8 and Example 2 is that the filler is composed of expanded graphite, sea-island fiber, and porous nano-silica in a weight ratio of 1:0.3:1, wherein the particle size of the porous nano-silica is 500nm, the average particle size of the expanded graphite is 10 microns, the average length of the worms is 50 microns, and the diameter of the sea-island fiber is 3D and the length is 0.5mm.
[0038] Example 9 The difference between Example 9 and Example 2 is that the filler is composed of expanded graphite, sea-island fiber, and porous nano-silica in a weight ratio of 1.7:0.5:1, wherein the particle size of the porous nano-silica is 200nm, the average particle size of the expanded graphite is 20 microns, the average length of the worms is 100 microns, and the diameter of the sea-island fiber is 4D and the length is 1mm.
[0039] Example 10 The difference between Example 10 and Example 2 is that the filler is composed of expanded graphite, sea-island fiber, and porous nano-silica in a weight ratio of 1.7:0.5:1, wherein the particle size of the porous nano-silica is 50nm, the average particle size of the expanded graphite is 30 microns, the average length of the worms is 180 microns, and the diameter of the sea-island fiber is 5D and the length is 1.5mm.
[0040] Embodiment 11 The difference between Example 11 and Example 9 is that the dispersant is a silane coupling agent solution, and the silane coupling agent solution is obtained by uniformly mixing KH550 silane coupling agent and water in a weight ratio of 1:1.
[0041] Example 12 The difference between Example 12 and Example 9 is that the dispersant is prepared by the following method: 0.1 kg of polyisobutylene succinimide, 0.8 kg of polyethylene glycol, 3 kg of 3-isocyanate propylmethyldimethoxysilane, 0.5 kg of acryloylethyl sulfobetaine and 5 kg of ethyl acetate were mixed and stirred at a speed of 100 r / min for 10 min to fully mix and obtain a dispersant.
[0042] Example 13 The difference between Example 13 and Example 12 is that the dispersant is prepared by the following method: 0.4 kg of polyisobutylene succinimide, 0.5 kg of polyethylene glycol, 2.5 kg of 3-isocyanate propylmethyldimethoxysilane, 0.8 kg of acryloylethyl sulfobetaine and 7 kg of ethyl acetate were mixed and stirred at a speed of 100 r / min for 10 min to fully mix and obtain a dispersant.
[0043] Embodiment 14 The difference between Example 14 and Example 12 is that the dispersant is prepared by the following method: 0.5 kg of polyisobutylene succinimide, 0.1 kg of polyethylene glycol, 1 kg of 3-isocyanate propylmethyldimethoxysilane, 1.5 kg of acryloylethyl sulfobetaine and 8 kg of ethyl acetate were mixed and stirred at a speed of 100 r / min for 10 min to fully mix and obtain a dispersant.
[0044] Embodiment 15 The difference between Example 15 and Example 14 is that polyethylene glycol is replaced by polyisobutylene succinimide in an equal amount.
[0045] Example 16 The difference between Example 16 and Example 14 is that 3-isocyanatepropylmethyldimethoxysilane is replaced by methacryloylethylsulfobetaine in an equal amount.
[0046] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that an equal amount of EVA latex is replaced by a polyurethane prepolymer.
[0047] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the polyurethane elastomer and the chain extender are replaced by EVA latex in equal amounts.
[0048] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the dispersant is replaced by EVA latex in equal amounts.
[0049] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the filler is nano-silicon dioxide.
[0050] Performance testing The sole slurry obtained in Examples 1-16 and 1-4 was placed in a vacuum degassing machine for degassing, then poured into a mold, placed in a vulcanizer and pressurized to 30 MPa, heated to 115°C, and a corresponding test sample was formed in the mold after 10 minutes. The test sample was taken out of the mold and placed at room temperature for 24 hours to obtain a test sample for the following experiment.
[0051] Test method / test method Rebound rate: refer to GBT1681-2009 "Determination of rebound elasticity of vulcanized rubber" for testing samples.
[0052] Wear amount: Refer to GB / T1689-1998 "Determination of wear resistance of vulcanized rubber" for testing samples.
[0053] Compression set: Test samples according to GB / T7759.2-2014 "Determination of compression set of vulcanized rubber or thermoplastic rubber".
[0054] Compression resistance: For the soles obtained in Examples 1-16 and 1-4, point A is marked at the heel, and the thickness of the sole at point A of the heel is measured. The sole is evenly pressed down to the upper surface of the sole with a force of 200 kg, and the pressure is maintained for 3 days at a temperature of 30°C and a humidity of 65%. After the force is removed, the sole is placed stably for 30 minutes at a temperature of 30°C and a humidity of 65%. The thickness of the sole at point A of the heel is measured again, and the change rate of the thickness of the sole before and after is calculated to obtain the compression resistance change rate. The compression resistance change rate is equal to the front thickness minus the rear thickness, multiplied by 100%. The greater the compression resistance change rate, the worse the compression resistance effect; Table 2 Experimental data of Examples 1-16 and Comparative Examples 1-4 Combining Example 1 and Comparative Examples 1-4 and Table 2, it can be seen that the wear amount and compressive resistance change rate of Comparative Examples 1-4 are higher than those of Example 1, while the rebound rate and compression permanent deformation rate are lower than those of Example 1, indicating that the use of the raw material system of the present application cooperates with each other to make the overall performance of the sole better.
[0055] Combining Example 2 with Examples 8-10 and Table 2, it can be seen that the wear amount and compressive resistance change rate of Examples 8-10 are lower than those of Example 2, while the rebound rate and compression permanent deformation rate are higher than those of Example 2, indicating that the expanded graphite, sea-island fiber, and porous nano-silica are compounded to play a synergistic role, and combined with the raw material system of the sole material to form a special support structure, thereby improving the comprehensive performance of the sole.
[0056] Combining Examples 12-14 with Example 9 and Table 2, it can be seen that the wear amount and compressive resistance change rate of Examples 12-14 are lower than those of Example 9, while the rebound rate and compression permanent deformation rate are higher than those of Example 9, indicating that the compounding of polyisobutylene succinimide, polyethylene glycol, 3-isocyanate propylmethyldimethoxysilane, and acryloylethyl sulfobetaine has a synergistic effect in promoting dispersion, and can improve the compatibility and dispersion uniformity of the filler in the raw material system, thereby further improving the comprehensive performance of the sole.
[0057] Combining Examples 15-16 with Example 12 and Table 2, it can be seen that the wear amount and compressive change rate of Examples 15-16 are higher than those of Example 12, while the rebound rate and compression permanent deformation rate are lower than those of Example 12, indicating that the compounding of polyisobutylene succinimide, polyethylene glycol, 3-isocyanate propylmethyldimethoxysilane, and acryloylethyl sulfonyl betaine has a better synergistic effect, so that it can be fully mixed with the raw material system of the sole, further improving the cushioning and shock absorbing performance and wear resistance of the sole, maintaining a better ventilation effect, and improving the comfort and durability of the sole.
[0058] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A shock-absorbing and ventilating venting sole, comprising a shoe body, characterized in that: The shoe body is provided with a plurality of interconnected cavity structures, and the shoe body is made of raw materials in weight percentage: EVA latex 25-50% Polyurethane prepolymer 24-50% Chain extender 5-15% Dispersant 1-8% Processing aids 1-3% Filler 1-20%; The total weight percentage of the EVA latex, polyurethane prepolymer, chain extender, dispersant, processing aid and filler is 100%; The filler is one or more of expanded graphite, carbon nanotubes, sea-island fibers, and porous nano-silicon dioxide.
2. A shock-absorbing and ventilating venting sole according to claim 1, characterized in that: The filler is composed of expanded graphite, sea island fiber and porous nano-silicon dioxide in a weight ratio of (1-2.3): (0.3-1.2):
1.
3. The shock-absorbing and ventilating venting sole according to claim 1, characterized in that: The particle size of the expanded graphite is 10-30 microns, and the worm length is 50-180 microns.
4. The shock-absorbing and ventilating venting sole according to claim 1, characterized in that: The sea island fiber has a line diameter of 3-5D and a length of 0.5-1.5 mm.
5. The shock-absorbing and ventilating venting sole according to claim 1, characterized in that: The particle size of the porous nano-silicon dioxide is 50-500nm, and the particle size of the carbon nanotube is 10-100nm.
6. A shock-absorbing and ventilating ventilating sole according to any one of claims 1 to 5, characterized in that: The dispersant is a polyethylene glycol solution or a silane coupling agent solution.
7. The shock-absorbing and ventilating venting sole according to claim 1, characterized in that: The dispersant is prepared from the following raw materials in parts by weight: Polyisobutylene succinimide 0.1-0.5 parts Polyethylene glycol 0.1-0.8 parts 1-3 parts of 3-isocyanate propylmethyl dimethoxysilane Methacryloylethyl sulfobetaine 0.5-1.5 parts 5-8 parts of ethyl acetate.
8. The shock-absorbing and ventilating shoe sole according to claim 7, characterized in that: The dispersant is prepared by the following method: Weigh 0.1-0.5 parts of polyisobutylene succinimide, 0.1-0.8 parts of polyethylene glycol, 1-3 parts of 3-isocyanate propylmethyldimethoxysilane, 0.5-1.5 parts of methacryloylethyl sulfobetaine, and 5-8 parts of ethyl acetate, and mix them evenly to obtain a dispersant.
9. The shock-absorbing and ventilating venting sole according to claim 1, characterized in that: The processing aid is one or more of an antioxidant, a mold release agent, a foaming agent, a defoaming agent, and a catalyst.
10. A method for preparing a shock-absorbing and ventilating ventilating shoe sole according to any one of claims 1 to 9, characterized in that: Prepared by the following method: According to weight percentage, the filler and the dispersant are weighed and mixed evenly to obtain a mixture A; According to weight percentage, 24-50% of polyurethane prepolymer, 5-15% of chain extender, and 1-3% of processing aid are weighed and mixed with all the mixture A, and after the reaction, 25-50% of EVA latex is added and mixed to obtain a shoe sole slurry; The shoe sole slurry is poured into the mold and solidified to form a shoe sole embryo in the mold, and a plurality of interconnected cavity structures are formed inside the shoe sole embryo to obtain the shoe sole.
Citation Information
Patent Citations
Carbon fiber-reinforced resin composition and molded article thereof
JP2012255063A
Carbon fiber-reinforced flame-retardant polycarbonate-based resin composition, and molded article
JP2014080564A
Rubber composition for shoes outsole having abrasion resistance and anti slip function
KR102092723B1
Composite comprising an elastomer comprising rubber particles and a foam layer
WO2024134119A1